1986
DOI: 10.3109/02713688608995159
|View full text |Cite
|
Sign up to set email alerts
|

Photically-induced retinal damage in diabetic rats

Abstract: The present study examines the interaction of light damage to the retina and streptozotocin (SZ)-induced diabetes in male and female rats during the early development of the disease, when changes occur in the blood-retinal barrier and in pigment cell membranes. Exposure of rats to low illuminance was used to determine the relationship between photically-induced cell death and diabetes. Other groups of animals were exposed to a greater illuminance for shorter time periods (24 hours) in attempts to identify a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…30 Other research has shown similar changes in the retinal pigment epithelium after albino rats were exposed to a brief period of intense light 19 or to longer periods of continuous, low-intensity visible light. 17 In this study, we found very few patients (0.62%) who developed PR after cataract surgery. This frequency is low compared with rates in previous investigations, which may be the consequence of improved operative techniques with more frequent use of phacoemulsification in cataract surgery.…”
Section: Discussionmentioning
confidence: 93%
“…30 Other research has shown similar changes in the retinal pigment epithelium after albino rats were exposed to a brief period of intense light 19 or to longer periods of continuous, low-intensity visible light. 17 In this study, we found very few patients (0.62%) who developed PR after cataract surgery. This frequency is low compared with rates in previous investigations, which may be the consequence of improved operative techniques with more frequent use of phacoemulsification in cataract surgery.…”
Section: Discussionmentioning
confidence: 93%
“…Under anesthesia, a 2-hour exposure to 1 mW/cm 2 of 463-nm radiation produced extensive damage to the retinal pigmented epithelium. In comparison to rats maintained under 750 lux (0.11 mW/cm 2 ), 14:10 light-dark cycle, a significant reduction in thickness of the outer nuclear layer was noted in rats maintained under 1080 lux (0.16 mW/cm 2 ) constant light for 9 days or longer [Johnson et al 1986]. It has also been demonstrated that long term light history of animals determined the sensitivity of the photoreceptors to light damage [Birch andJacobs 1980, Noell andAlbrecht 1971].…”
Section: Technical Reportmentioning
confidence: 86%
“…This is consistent with other studies that have shown electrophysiological changes of ERG and VEP after photostress in diabetes type 1 without retinopathy [ 43 ]. Also histological analyses have shown reduced outer nuclear layer after a period of 9 days of light exposure in streptozotocin injected animals when compared to control group [ 44 ]. Other studies have reported that retinal deterioration due to white light was so severe in diabetic group after 42 days of light exposure to 1500-2000 mW/ m² during a 12 to 12 hour light-dark cycle, that ERG could not be recorded.…”
Section: Discussionmentioning
confidence: 99%